Keefektifan Konseling Kelompok dengan Teknik Desensitisasi Sistematis dalam Mereduksi Sifat FoMO (Fear of Missing Out) pada Mahasiswa - Tri Anggraini; Zhila Jannati; Bela Janare Putra (Scidacplus, 2024)
This research is entitled “The Effectiveness of Group Counseling with Systematic Desensitization Techniques in Reducing FoMO (Fear of Missing Out) in Students